Odpowiedzi

Najlepsza Odpowiedź!
2010-01-16T18:36:06+01:00
1.
1/5 + (-0,8)* 1 /14 - 0,2=
= 1/5 + (- 8/10)*1/14 - 2/10=
= 1/5 - 2/35 - 1/5=
= -2/35


2.
[-0,5 * 3 : ( - 1/2 ) : ( - 0,1 ) ] : ( -60 )=
=[(-1/2)*3 *(-2)*(-10)] : (-60)=
=[ ( -3/2)*(-2)*(-10)] : (-60)=
= [ -30] : (-60)=
= 1/2


3.
-4, 75 + 2 1/9 * ( - 2/ 9 )=
=- 4 i 3/4 + 19/9*(-2/9)=
=- 19/4 +( 19/9)*(-2/9)=
= -19/4 -19/18=
= -171/36 - 38/36=
= - 209/36=
= - 5 i 29/36


4.
[ - 2, 5 -(-1/4)]:(-1,5 )=
=[ -2,5 + 0,25 ] : (-1,5)=
= [ - 2,25 ] : (-1,5)=
= 1,5


5.
-0,8 :9/10 + 5 * 0, 48=
= (-4/5)*(10/9) + 2,4=
= (-8/9)+ 24/10=
= (- 8/9) + 12/5=
= (-40/45 ) + 108/45=
= 68/45 =
= 1 i 23/45


6.
144 :[10+(-1/4-3,75):2]:(-3-15) =
= 144 : [ 10 + (-0,25 -3,75 ) : 2] : (-18)=
= 144 : [ 10 - 4 ] :2 ] : (-18)=
= 144 : [ 6 : 2 ] : (-18)=
= 144 : [ 3 : (-18) ]=
= 144 : (-1/6) =
= 144*(-6)=
= - 864